Change of Performance in Mimicking Oral Reading Practice - IIMURA, Hideki; TAKANAMI, Sachiyo (ARELE: Annual Review of English Language Education in Japan, 2020)
When oral reading practice is used in the classroom, teachers usually set a goal for students in terms of frequency (e.g., how many times to read) or duration (e.g., for how long to read). Yet such goals are often ineffective in improving oral reading performance and general English skills because the amount of oral reading practice required to improve varies according to learners’ level. In order to resolve this problem, we devised a new type of learning activity, called mimicking oral reading practice (MORP). In MORP, the learning goal is clear, simple, and stable: to imitate the modeled speech as accurately as possible. This is the only requirement for the learners. Based on our previous studies (Iimura & Takanami, 2016; Takanami & Iimura, 2019), this study reports on how performance in MORP changed over a period of five weeks. The 18 Japanese university students who participated in the study were instructed to imitate a model reading and record their sound-data weekly. We assessed their recorded performance in mimicking the model speech in terms of (a) pronunciation, (b) intonation, and (c) speed. The results demonstrated that it would require a fair amount of time (i.e., at least four weeks) to improve their reading aloud performance significantly. Detailed tracking data, including participants’ feedback about mimicking practice, are reported in this article.